2017
DOI: 10.1080/00036846.2017.1279270
|View full text |Cite
|
Sign up to set email alerts
|

The law of small numbers: investigating the benefits of restricted auctions for public procurement

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…They find evidence that negotiations correlate with lower consumer surplus, increasing prices for similar services. Chever and Moore (2012) and Chever et al (2013) reach a different conclusion studying construction of social housing in France. They find that negotiations after an informal auction are associated with lower costs relative to open auctions.…”
Section: Related Literaturementioning
confidence: 99%
“…They find evidence that negotiations correlate with lower consumer surplus, increasing prices for similar services. Chever and Moore (2012) and Chever et al (2013) reach a different conclusion studying construction of social housing in France. They find that negotiations after an informal auction are associated with lower costs relative to open auctions.…”
Section: Related Literaturementioning
confidence: 99%
“…This result is robust when controlling for the geographical location, corruption, social capital, and judicial efficiency in the region of the public buyers that run the auctions. In the same vein, Chever et al (2017), with data on 180 calls for bids and contracts that were signed by a French local public buyer of social housing, found that limiting competition (i.e., restraining the number of responses to the call for bids) for small simple projects enables economies to be made on transaction costs without increasing procurement costs, corruption and favoritism.…”
Section: Box 5: Privatization and Mortalitymentioning
confidence: 97%
“…In the same vein, Chever et al. (), using data on 180 call for bids and contracts signed by a French local public buyer of social housing, found that limiting competition (i.e. restraining the number of responses to call for bids) for small simple projects enables economies to be made on transaction costs without increasing procurement costs or corruption and favouritism.…”
Section: Factors Influencing the Likelihood Of Performance Failure Inmentioning
confidence: 98%